2022
DOI: 10.2174/1386207325666220208122911
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-Based Signature to Predict the Development of Alzheimer’s Disease

Abstract: Background: Background: Patients with mild cognitive impairment (MCI) suffer from high risk of developing Alzheimer’s disease (AD). Cumulative evidence has demonstrated that development of AD is a complex process which could be modulated by miRNAs. Here, we aimed to identify miRNAs involved in the pathway, and interrogate their ability to predict prognosis in patients with MCI. Methods: Methods: We obtained the miRNA-seq profiles and the clinical characteristics of patients with MCI from the Gene Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Due to their role as genetic regulators, miRNAs are nowadays considered potential therapeutic tools for restoring cell functions disrupted during disease progression [ 14 16 ]. Previous studies have shown that specific sncRNAs have differential expression between AD patients and cognitively healthy participants [ 17 21 ], and some of them exhibit good predictive accuracy [ 22 ]. Furthermore, differential expression of sncRNAs has been observed between individuals with MCI and healthy participants [ 19 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their role as genetic regulators, miRNAs are nowadays considered potential therapeutic tools for restoring cell functions disrupted during disease progression [ 14 16 ]. Previous studies have shown that specific sncRNAs have differential expression between AD patients and cognitively healthy participants [ 17 21 ], and some of them exhibit good predictive accuracy [ 22 ]. Furthermore, differential expression of sncRNAs has been observed between individuals with MCI and healthy participants [ 19 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different types of dementia, Alzheimer's disease (AD) and vascular dementia (VaD) stand out as the most prevalent [3]. Obesity entails several detrimental consequences in the brain, including impaired synaptic plasticity, reduced brain volume, low-grade inflammation and Nutrients 2024, 16, 955 2 of 14 neurodegeneration, that can contribute to AD and other types of dementia [4]. Obesity, but especially central obesity, is commonly found in patients with T2D and it is closely associated with insulin resistance (IR) in peripheral tissues [5].…”
Section: Introductionmentioning
confidence: 99%
“…Others, such as miR-125b-5p and miR-20b-5p, found in high levels in the hippocampus, were associated with memory impairment [14,15]. Several miRNA signatures, discriminating AD dementia patients from individuals without AD dementia or predicting the conversion in patients from mild-cognitive impairment to AD dementia with high accuracy, were described [16,17]. miRNAs, including miR-29a-3p, miR-34a, miR-125b-5p and miR-20b-5p, within others, have been also related to insulin secretion, beta cell development and the regulation of the insulin signaling pathway [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Again, some miRNAs families as miR-132 and/or miR-134 were shown to be deregulated in MCI patients, speci cally miR-132 for its involvement in tau metabolism through IT PKB gene (Inositol-Trisphosphate 3-Kinase B) targeting [7]. LncRNAs are mRNA-like transcripts (200 nt to > 100 kb), with a biogenesis process similar to mRNAs, but different from them for the lack of an open reading frame (ORF) of signi cant length and the absence of a translation capacity [8].…”
Section: Introductionmentioning
confidence: 99%